Rural Development: A Legacy Continues… - Abu, Roziya; Ahmad Sabri, Ahmad Zaharuddin Sani (Tun Dr. Mahathir Mohamad Thoughts Institute (IPDM), 2017)
Traditionally, rural developments are centered on the intensive utilization of land natural resources such as agriculture and farming. Hence due to the globalization of production networks and urbanization, rural development is now about improving the quality of life and economic well-being of people living in remote and sparsely populated areas. These include economics, social and leadership improvements. Malaysia - home to the three great diasporic communities – Malays, Chinese and Indians, has always and will always being judge and asses us by the way we manage our internal economics, political and racial relationship. Notwithstanding, Malaysia has successfully transformed by Tun Abdul Razak Hussein’s enlightened recruitment of talent. Under his supervision and approach to leadership, economics and communal racial issues, many young rural Malaysian has step up and becomes qualified leaders and economist – passionate and committed to Malaysian development. His legacy continues with his son- our own Prime Minister Dato’ Seri Najib Tun Abdul Razak. Realizing the percentages of rural Malaysian lived below poverty line, he and his government accelerate with more plans and progression upon improving the quality of lives and incomes for all rural Malaysian. The introduction of new opportunities, entrepreneurships and many economics and social growth, have effectively boost the sustainability standards of living amongst Malaysian rural community. This paper will enlighten further the successful effort, struggle and determination done by both excellent leaders - Tun Abdul Razak Hussein and Dato’ Seri Najib Tun Abdul Razak in supporting rural Malaysian Development.